"Fou rire prodromique" heralding a brainstem stroke. Issue 2 (February 1993) - Wali, G M
Abstract : A patient manifested pathological laughter heralding the onset of brainstem stroke leading to a "locked-in" state. The pathological laughter did not recur. MRI revealed a bilateral ventral pontine infarct. The clinico-anatomical correlations of this rare phenomenon of fou rire prodromique are discussed.